Differences in haemosporidian parasite prevalence and diversity in migratory and resident birds of prey species revealed by a non-invasive sampling method. - Bukauskaitė, Dovilė; Dementavičius, Deivis; Rumbutis, Saulius; Treinys, Rimgaudas (Ecology and Evolution, 2024)
Avian haemosporidian parasites are widespread globally and infect numerous wild bird species. However, they have primarily been studied in passerine birds. Accordingly, the prevalence and diversity of these parasites in birds of prey remain understudied. This lack of research is primarily due to the international protection status of many of these species, their sparse distribution across ecosystems and difficulty to capture in the wild. The aim of this study was to examine the prevalence and diversity of haemosporidian parasites in two species of birds of prey, namely white-tailed eagle and lesser spotted eagle. To achieve this, a non-invasive approach was employed, involving the extraction of DNA from blood spots present in moulted feathers. Freshly moulted feathers were collected from the ground under nests or within the nests of these birds during the breeding season. A visible blood spot located at the junction of the calamus and rachis was removed and fixed in SET buffer for molecular analysis. The identification of haemosporidian parasites (Plasmodium, Haemoproteus and Leucocytozoon) was conducted using PCR-based methods. Overall, parasite DNA was successfully detected in shed feathers that were kept in their original form at least decade prior to analysis. Among the studied individuals, resident white-tailed eagles showed significantly lower infection rates of haemosporidian parasites compared to migratory lesser spotted eagles. A total of nine genetic lineages of haemosporidian parasites were detected, with seven of them being new to science based on partial sequences of the cytb gene. Additionally, the phylogenetic relationships among these new lineages and previously described ones were established. These findings highlight the suitability of non-invasive sampling for investigating the prevalence and diversity of haemosporidian parasites in wild birds of prey populations. Moreover, this approach holds promise for studying other challenging-to-reach and protected bird species. According to our research, there is a greater chance of finding haemosporidian parasites in freshly gathered feathers.